Membrane-Depolarizing Channel Blockers Induce Selective Glioma Cell Death by Impairing Nutrient Transport and Unfolded Protein/Amino Acid Responses - Niklasson, Mia; Maddalo, Gianluca; Sramkova, Zuzana; Mutlu, Ercan; Wee, Shimei; Sekyrova, Petra; Schmidt, Linnéa; Fritz, Nicolas; Dehnisch, Ivar; Kyriatzis, Gregorios; Krafcikova, Michaela; Carson, Brittany B; et al. (Cancer research, 2017)
Glioma-initiating cells (GIC) are considered the underlying cause of recurrences of aggressive glioblastomas, replenishing the tumor population and undermining the efficacy of conventional chemotherapy. Here we report the discovery that inhibiting T-type voltage-gated Ca(2+) and KCa channels can effectively induce selective cell death of GIC and increase host survival in an orthotopic mouse model of human glioma. At present, the precise cellular pathways affected by the drugs affecting these channels are unknown. However, using cell-based assays and integrated proteomics, phosphoproteomics, and transcriptomics analyses, we identified the downstream signaling events these drugs affect. Changes in plasma membrane depolarization and elevated intracellular Na(+), which compromised Na(+)-dependent nutrient transport, were documented. Deficits in nutrient deficit acted in turn to trigger the unfolded protein response and the amino acid response, leading ultimately to nutrient starvation and GIC cell death. Our results suggest new therapeutic targets to attack aggressive gliomas. Cancer Res; 77(7); 1741-52. ©2017 AACR.
Keywords: Animals; Mycotoxins; biologický transport; gliom; Calcium Channels, T-Type; Sodium; Cell Line, Tumor; nádorové buněčné linie; nádory mozku; lidé; blokátory kalciových kanálů; proteomika; Mice; Dihydropyridines; mykotoxiny; Glioma; myši; buněčná smrt; Humans; Biological Transport; Proteomics; Potassium Channels, Calcium-Activated; sodík; Neoplastic Stem Cells; draslíkové kanály aktivované vápníkem; Calcium Channel Blockers; Cell Death; dihydropyridiny; Brain Neoplasms; Amino Acids; signální dráha UPR; zvířata; aminokyseliny; Unfolded Protein Response; nádorové kmenové buňky; vápníkové kanály - typ T